Gender disparities in access to pediatric renal transplantation in Europe: data from the ESPN/ERA-EDTA registry - Hogan, Julien; Couchoud, C.; Bonthuis, M.; Groothoff, J. W.; Jager, K. J.; Schaefer, Franz; Stralen, K. J. Van (American journal of transplantation, 2016)
Inequalities between genders in access to transplantation have been demonstrated. We aimed to validate this gender inequality in a large pediatric population and to investigate its causes. This cohort study included 6454 patients starting renal replacement therapy before 18 years old, in 35 countries participating in the European Society for Paediatric Nephrology/European Renal Association-European Dialysis and Transplant Association Registry. We used cumulative incidence competing risk and proportional hazards frailty models to study the time to receive a transplant and hierarchical logistic regression to investigate access to preemptive transplantation. Girls had a slower access to renal transplantation because of a 23% lower probability of receiving preemptive transplantation. We found a longer follow-up time before renal replacement therapy in boys compared with girls despite a similar estimated glomerular filtration rate at first appointment. Girls tend to progress faster toward end-stage renal disease than boys, which may contribute to a shorter time available for pretransplantation workup. Overall, medical factors explained only 70% of the gender difference. In Europe, girls have less access to preemptive transplantation for reasons that are only partially related to medical factors. Nonmedical factors such as patient motivation and parent and physician attitudes toward transplantation and organ donation may contribute to this inequality. Our study should raise awareness for the management of girls with renal diseases.